HCV related severe cryoglobulinemic vasculitis treated with plasma exchange and rituximab: case report and literature review - Snezana Arandjelovic; Branka Bonaci-Nikolic; Aleksandra Peric-Popadic; Vesna Tomic-Spiric; Jasna Bolpacic; Sanvila Raskovic; Sladjana Andrejevic (Journal of Infection in Developing Countries)
Mixed cryoglobulinemia is the most prevalent extrahepatic manifestation of chronic HCV infection. It is usually a benign lymphoproliferative disorder which presents as vasculitis affecting different organs. Although life-threatening cryoglobulinemic vasculitis (CryoVas) is rare, it is sometimes the first and possibly lethal complication. Its treatment depends on the severity of vasculitis and can be challenging. High dose of corticosteroids, immunosuppressive agents and plasma exchange represent the first-line treatment, which should be followed by antiviral therapy. Rituximab is an effective and safe treatment option. However, the data about its use in life-threatening conditions are scarce. We report the case of a patient with severe, relapsing and life-threatening HCV-related CryoVas  resistant to standard therapy who had had an initial beneficial response to rituximab added to plasma exchange that was later compromised by the development of sepsis. We also review the literature and discuss manifestations and therapy of life-threatening Cryovas with focus on rituximab use.